A Novel Method to Predict Phase Fraction Based on the Solidification Time on the Cooling Curve - Junfeng Xu; Yindong Fang; Tian Yang; Changlin Yang (Metals, 2025)
The phase fraction plays a critical role in determining the solidification characteristics of metallic alloys. In this study, we propose a novel method (fs = (t − tl)/(ts − tl)) for estimating the phase fraction based on the solidification time in cooling curves. This method was validated through an experimental analysis of Al-18 wt%Cu and Fe42Ni42B16 alloys, where the phase fractions derived from cooling curves were compared with quantitative microstructure evaluations using computer-aided image analysis and the box-counting method. Then, a comparison between the analysis using the present novel method and Newtonian thermal analysis demonstrates good agreement between the results. The present method is easier to operate, since it does not need derivative and integral operations as in Newtonian thermal analysis. In addition, based on the characteristics of the cooling curve, we also found two other relationships—V/Rc = D/ΔTc and RΔt = constant, where V is the solidification rate, Rc is the recalescence rate, D is the diameter of the focal area of the pyrometer, ΔTc is the recalescence height, R is the cooling rate, and Δt is the solidification plateau time. These findings establish an operational framework for quantifying phase fractions and solidification rates in rapid solidification.